Situation Report: Hungary, 15 February 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Senior HSWP official Visits the USA / by Alfred Reisch Media Coverage of the Torun Trial / by Edith Markos Crisis Brewing in Writers' Union / by Alfred Reisch West German Company Has Majority Holding in New Joint Venture / by Alfred Reisch Private Hotel Opens / by Eva Lengyel Population Decline Presents Growing Cause for Concern / by Steven Koppany The Wages of Sin: Prostitution / by Eva Lengyel